REVALUATION OF TRADITIONAL PERFORMING ARTS IN THE POST-INDEPENDENT INDIAN THEATRE - BURLA, VENKATA NARESH; Yadav, Sudarshan (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Traditional performing arts are one of the important genres of folklore. Historically, since ancient times, the performing arts were used by the people for fulfilling their demands from rituals to entertainment. These forms had played a vital role in the construction of socio- cultural history in India. Interestingly, the ancient Indian society maintained both the folk and classical traditions equally with full enthusiasm. But with the onset of western theatre during colonial period, the traditional arts had been neglected. The almost forgotten traditional forms found new life with the emergence of freedom movements that made use of both traditional and modern forms. In the post-independence scenario, the values of these forms have been reinstated as they are the medium to construct or assert the cultural identity of different communities and the nation. Due to efforts of government of India, IPTA and other independent artistes, the folk-art tradition got revived in performing arts. Taking insights from various secondary sources and referring to the interviews (of the stalwarts of performing arts in India) put in the book Contemporary Indian Theatre of Sangeet Natak Akademi, this paper attempts to understand the process of revaluation and the emergence of new audience along with intellectual support for the folk theatre traditions. This paper also focuses on the various issues that have made impact on the structure and functions of these forms in the past few centuries with the special focus on the present status of folk forms. In doing so, references of the past experimentations and recent ones are made. The folk-art forms and traditions got transformed and to an extent devalued after the coming of cable/satellite television and social media. But this era is marked by some new experimentation in folk art and performing art traditions which is being referred to in this paper.